Circulating Total Cell-Free DNA Levels Are Increased in Hypertensive Disorders of Pregnancy and Associated with Prohypertensive Factors and Adverse Clinical Outcomes - Amaral, Lorena M.; Sandrim, Valeria C. [UNESP]; Kutcher, Matthew E.; Spradley, Frank T.; Cavalli, Ricardo C.; Tanus-Santos, Jose E.; Palei, Ana C. (Mdpi, 2021)
Previous studies have described increased circulating cell-free DNA (cfDNA) in hypertensive disorders of pregnancy (HDP). Here, we aimed first to confirm this information using a simple, but sensible fluorescent assay, and second to investigate whether total cfDNA is associated with circulating factors known to be linked to the pathophysiology of HDP as well as with poor maternal-fetal outcomes. We studied 98 women with healthy pregnancies (HP), 88 with gestational hypertension (GH), and 91 with preeclampsia (PE). Total DNA was extracted from plasma using the QIAamp DNA blood mini kit and quantified using Quant-iT (TM) PicoGreen(R) dsDNA fluorescent detection kit. We found higher total cfDNA levels in GH and PE (197.0 and 174.2 ng/mL, respectively) than in HP (140.5 ng/mL; both p < 0.0001). Interestingly, total cfDNA levels were elevated in both male and female-bearing pregnancies diagnosed with either HDP, and in more severe versus less severe HDP cases, as classified according to responsiveness to antihypertensive therapy. In addition, total cfDNA was independently associated with HDP, and a cutoff concentration of 160 ng/mL provided appropriate sensitivity and specificity values for diagnosing GH and PE compared to HP (70-85%, both p < 0.0001). Moreover, high total cfDNA was associated with adverse clinical outcomes (high blood pressure, low platelet count, preterm delivery, fetal growth restriction) and high prohypertensive factors (sFLT-1, sEndoglin, MMP-2). These findings represent a step towards to the establishment of cfDNA as a diagnostic tool and the need to understand its role in HDP.
Keywords: adverse maternal-fetal outcomes; biomarkers; cell-free DNA; gestational hypertension; preeclampsia